Effect of using one versus two growth-promoting implants during the suckling period on the weaning weights of nursing calves - L.R. Corah; R.T. Wary; F. Schwartz; M. McKee; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1978)
Three trials were conducted to study the effect on calf weight gains from using two 36-mg. Ralgro implants during the suckling period. Two Ralgro implants 60 to 90 days apart improved the average weight gain during the suckling period by 39.4, 43, and 46.6 pounds for the three trials. A single Ralgro implant improved suckling gains by 33.5, 22.1, 28.4 and 27.9 lbs. for the four test groups. Ralgro implants used at birth gave the same response as when first used when calves were 4 months old. A 15-mg. DES implant used in trial one improved suckling gains 23.4 lbs. These results suggest that at least one implant during the suckling period is a management practice cow-herd operators cannot afford to forego. Two implants during the suckling period give an even more economical response.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Growth implants; Weaning weights; Nursing calves